EFEKTIVITAS DAN EFISIENSI KEGIATAN KELOMPOK KERJA GURU PENDIDIKAN AGAMA ISLAM SEKOLAH DASAR (KKG PAI SD) DALAM MENINGKATKAN PROFESIONALITAS GURU DI KECAMATAN NGAWEN KABUPATEN BLORA - Achmad Abdul Azis (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2019)
he effectiveness and efficiency of the work activities of elementary school Islamic religion teacher training groups is a measure of success that has been determined in the achievement of the PAI elementary teacher organization program activities. And trying to find good ways to achieve these goals with various efforts including through education, training and coaching such as the KKG. The objectives in this study are (1) To find out the effectiveness and efficiency of the implementation of the KKG PAI SD program activities in increasing teacher professionalism in Ngawen District, Blora Regency (2) To find out the supporting and inhibiting factors of the effectiveness and efficiency of SD PAI KKG activities in increasing the professionalism of teachers in Ngawen District Blora District (3) To find out the efforts to overcome obstacles in the effectiveness and efficiency of KKG PAI SD activities in increasing the professionalism of teachers in Ngawen District, Blora Regency. The method in this research is qualitative research with the type of field research (field research) respondents determined through purposive sampling techniques and data collection techniques used are observation, interviews, and documentation. While the data analysis technique is done in several steps, namely reducing data, displaying data, and drawing conclusions. The results of this study indicate that: (1) The effectiveness and efficiency of the implementation of the KKG PAI SD program activities in the Ngawen District of Blora Regency is very effective and efficient in increasing teacher professionalism, among others: adding insight, knowledge, and ability of PAI SD teachers in improving the quality of the learning process in class, teachers can work together in the preparation of learning tools, teachers can master in depth the material to be taught to students (2) Supporting and inhibiting factors of KKG PAI SD activities in increasing the professionalism of teacher teachers in Ngawen District, Blora Regency, for supporting factors between others: (a) educational factors, (b) age factors, (c) motivation factors. Inhibiting factors in the implementation of KKG PAI SD activities in increasing teacher professionalism in Ngawen District, Blora Regency, include: (a) facilities and infrastructure factors, (b) funding factors, (c) IT mastery factors that have not been maximally and evenly distributed (3) The solution what can be done is that the SDG KKG PAI is more intense in the use of technology as a learning medium, it remains consistent as a forum for professional guidance of PAI teachers and the KKG PAI SD needs to be optimally organized and sustainable empowered.